Criminal Liability for Harmful Acts of Artificial Intelligence in the Palestinian and Italian Legal Systems - Farah Thulthen; Tania Alkhatib; Issa Issa; Aisha Abd Al Hafeeth; Diaa Awad; Mohammad Jarrar (International Journal of Law Research and Studies, 2026)
Purpose: This study aimed to analyze the concept of artificial intelligence (AI), its developments, and its various applications within legal contexts, and to examine the frameworks of criminal liability for parties associated with AI under Palestinian and Italian law. It also highlighted legislative gaps and legal practices in addressing harmful acts arising from these technologies and provided legal recommendations to ensure a balance between protecting society and promoting technological innovation. Methodology: The researchers employed a comparative approach between the Palestinian and Italian legal systems, using a descriptive-analytical method to examine relevant laws, statutory texts, and judicial practices where available. The study also relied on a review of contemporary legal literature and jurisprudence. Findings: The study found that criminal liability for harmful acts caused by AI is primarily linked to the intent and actions of human parties involved in the design and operation of AI applications. Current Palestinian and Italian laws do not recognize independent liability for the AI applications themselves. Recommendations: The study recommended establishing clear legislative frameworks that define the responsibilities of programmers, owners, and operators when using AI applications, and promoting adherence to technical and ethical safety standards to protect society without hindering technological development.